Numerical analysis of marine propellers low frequency noise during maneuvering. (January 2021) - Dubbioso, Giulio; Muscari, Roberto; Ortolani, Fabrizio; Di Mascio, Andrea
Abstract: In this paper the effects of maneuvering motion on the hydro–acoustic performance of a marine propeller in behind–hull configuration is investigated. Velocities induced by ship motions markedly modify the inflow to the propeller and hence noise sources and emission can be different with respect to the rectilinear motion, that traditionally is exclusively considered during the design process. This problem is crucial from a practical perspective, because the success of many types of operations at sea relies on the stealthy qualities of the vehicle and, moreover, for it can provide an additional aid to preserve marine life. In this paper this topic is tackled by a multidisciplinary approach that involves the use of hydrodynamic solvers and an acoustic analogy based on the Formulation 1A by Farassat. In particular, the noise sources, input to the acoustic analogy, are computed by an hybrid approach consisting of CFD simulation to obtain the inflow to the propellers and a blade element momentum theory solver ( B E M T ), enhanced with linear, partially cavitating hydrofoil theory to account for cavitating conditions too. The test case is a modern twin screw ship undergoing rectilinear advance and turning maneuvers at two different rudder angles for a moderate speed at F N = 0.265 .